"Following orders" as a critique on healthcare allocation committees: An anthropological perspective on the role of public memory in bioethical legitimacy. (28th July 2021) - Assor, Yael
Abstract: The public perception of decision‐making procedures as fair processes is a central means for establishing their legitimacy to make difficult resource allocation decisions. According to the ethical framework of accountability for reasonableness (A4R, hereafter), which specifies conditions for fair healthcare resource allocation, disagreements about what constitutes relevant considerations are a central threat to its perceived fairness. This article considers how an ethical principle grounded in the public memory of past traumatic events may become the topic of such disagreements. I demonstrate this through an anthropological case study of a recent public de bate concerning an Israeli healthcare allocation committee (HAC, thereafter), which determines state subsidies for new medical technologies as part of Israel's public healthcare system. Drawing upon ethnographic fieldwork about the HAC, I show how the public memory of Adolf Eichmann's trial constitutes a bioethical problem for the committee's legitimacy. Based on Arendt's and Bauman's writings that Nazi bureaucrats' manner of "following orders" was an ethical transgression, some patients contended that the committee has a historical responsibility to question its strict adherence to bureaucratic procedures. Since the committee did not have a direct link to the events of the Holocaust, other considerations seemed to them more relevant. I then present an offer that can settle this disagreement and maintain the HAC's legitimacy according to A4R. I conclude by discussing the contribution of empirical data to models of bioethical legitimacy. Abstract :